Low-wage jobs: Stepping stone or poverty trap? - Andreas Knabe; Alexander Plum (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
We examine whether low-paid jobs have an effect on the occupational advancement probability of unemployed persons to obtain better-paid jobs in the future (stepping-stone effect). We make use of data from the German Socio-Economic Panel (SOEP) and apply a dynamic random-effects probit model. Our results suggest that low-wage jobs can acts stepping stones to better-paid work. The improvement of the chance to obtain a high-wage job by accepting low-paid work is particularly large for less-skilled persons and for individuals with longer unemployment experiences. Low-paid work is less beneficial if the job is also associated with a low social status.
Keywords: J64; J62; J31; 330; low pay dynamics; unemployment dynamics; dynamic random effects models; state dependence; Niedriglohn; Berufliche Integration; Erwerbsverlauf; Schätzung; Deutschland